2021
DOI: 10.3390/nano11061547
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Nano-Crystallized Indium-Gallium-Zinc Oxide Thin Films Determined by Differential Three-Omega Method

Abstract: The temperature dependence thermal conductivity of the indium-gallium-zinc oxide (IGZO) thin films was investigated with the differential three-omega method for the clear demonstration of nanocrystallinity. The thin films were deposited on an alumina (α-Al2O3) substrate by direct current (DC) magnetron sputtering at different oxygen partial pressures ([PO2] = 0%, 10%, and 65%). Their thermal conductivities at room temperature were measured to be 1.65, 1.76, and 2.58 Wm−1K−1, respectively. The thermal conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Also, polycrystalline SnO 2 demonstrated a thermal conductivity between 25 and 40 W/(Km) [60]. As a comparison, IGZO demonstrates a thermal conductivity of ~1-8 W/(Km) in both an amorphous and crystalline state (i.e., CAAC-IGZO) [61][62][63]. The porosity and also the fabrication process of the material are important parameters in the thermal conductivity values [63].…”
Section: Discussionmentioning
confidence: 99%
“…Also, polycrystalline SnO 2 demonstrated a thermal conductivity between 25 and 40 W/(Km) [60]. As a comparison, IGZO demonstrates a thermal conductivity of ~1-8 W/(Km) in both an amorphous and crystalline state (i.e., CAAC-IGZO) [61][62][63]. The porosity and also the fabrication process of the material are important parameters in the thermal conductivity values [63].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Indium-gallium-zinc oxide (IGZO) is considered one of the most promising channel layer materials to meet the requirements of TFTs. [9][10][11][12][13][14][15][16][17][18][19][20] Unfortunately, indium is toxic and scarce, limiting its commercial application and making the device environmentally unfriendly and costly. 21,22 Moreover, it has been found that chemical composition has a considerable impact on the performance of IGZO TFTs, 23 and it is difficult to accurately control the composition of IGZO containing four components.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IGZO TFTs are used as a switching device in flat panel displays, such as active-matrix organic light-emitting diode (AMOLED) displays, active-matrix liquid crystal displays (AMOLCD) and electrophoretic displays [4,5]. Most of the studies are focused on the electrical, electronic, optical and thermal properties of IGZO thin films [6,7]. There are also several studies to improve these parameters for the transistors by using Dirac materials, with the tunneling and trapping effects as the main approach [8,9].…”
Section: Introductionmentioning
confidence: 99%